The 15th Lithuanian police battalion (1941–1944) - Bubnys , Arūnas (Genocidas ir rezistencija, 2007)
The history of the 15th Lithuanian Police Battalion can be divided into several stages: 1) the formation of the battalion in Vilnius (July 1941); 2) the service in Belarus (end of July 1941—June 1944); 3) its withdrawal to Lithuania and disbanding (July 1944). Throughout its existence the 15th Battalion was stationed almost exclusively in Belarus, guarding the railways and other objects of military importance, conveying prisoners of war, and fighting against Soviet partisans. Unlike other Lithuanian police battalions, this battalion did not commit any war crimes and was not involved in the killings of Jews. The only exception was when a platoon led by Lieutenant J. Stankus took part in the execution of 20 Belarusian supporters of Soviet partisans in Dereein in August 1942. Although the battalion took an active part in anti-partisan actions in 1942 and 1943, it did not sustain great losses: several fighters were killed in fights against partisans or due to accidents, an unknown number was injured, and several scores deserted the battalion. The battalion was distinguished by its discipline and training. Following the disbanding of the battalion, some of the fighters went on to serve in the Homeland Defence formations or German military units in Germany and Italy.